Effect of antioxidants on stability, nutritional values of refined sunflower oil during accelerated storage and thermal oxidation in frying - Akhtar, H; Tariq, I; Mahmood, S; Hamid, S; Khanum, R (Bangladesh Journal of Scientific and Industrial Research, 2012)
Untreated sunflower oil (without antioxidants) was much more affected during long storage as well as by the thermal oxidation in 4 hours frying process. The shelf life of oil was increased both during storage and in frying process at elevated temperature by the addition of synthetic antioxidants. TBHQ (Tertiory butyl hydroquinone) BHT (Butylated hydroxyl toluene) BHA (Butylatd hydroxyl amine) and the mixture of BHA and BHT used in the present study in 0.02, 0.02, 0.02 and 0.01+0.01 amount respectively to observe the stability of refined sunflower when stored at 30°C for 21 weeks in transparent PET bottles. The stored oils (treated and untreated) when underwent in the process of frying at the temperature of 180°C further deterioration of oils happened. The antioxidant activities and protective effects in stabilization of sunflower oils during storage and in frying process measured in terms of POV (peroxide), FFA (free fatty acids), p-AnV (p- Anisidine value), Colour Index, RI (Refractive index), and fatty acid profile. Result indicated that TBHQ exhibited stronger antioxidant activity during storage and gave maximum protection against thermal oxidation when oil subjected in the process of multiple frying for continous four hours at elevated temperature. The results were indicated the effectiveness of antioxidants in the order like TBHQ > BHT > BHA BHA+BHT. DOI: http://dx.doi.org/10.3329/bjsir.v47i2.11458 Bangladesh J. Sci. Ind. Res. 47(2), 223-230, 2012